Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/biom10081127
|View full text |Cite
|
Sign up to set email alerts
|

The Short Overview on the Relevance of Fatty Acids for Human Cardiovascular Disorders

Abstract: This review presents existing evidence of the influence of saturated and unsaturated fatty acids on cardiovascular diseases (CVD). Data are discussed regarding the roles of the most relevant fatty acids, such as myristic (C14:0), palmitic (C16:0), stearic (C18:0), palmitoleic (C16:1), oleic (C18:1), linoleic (C18:2), α-linolenic (C18:3, ω-3), γ-linolenic (C18:3, ω-6), arachidonic (C20:4), eicosapentaenoic (C20:5), docosahexaenoic (C22:6), and docosapentaenoic (C22:5) acid. The accumulated knowledge has expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 152 publications
3
61
0
3
Order By: Relevance
“…In this study, palmitic acid (C16:0) concentration was the highest among other SFAs in maternal and cord blood (Table 2). These findings are in line with previous studies which stated that palmitic acid is the principal constituent of fatty acids found in human tissues, such as in serum (Liu et al 2017;Yammine et al 2018), red blood cell (Aktas et al 2016), adipose tissue (Shramko et al 2020) and other human tissues in general (Ruiz-Nunez et al 2016). This pattern remains consistent when compared to Spanish vegetarian population (Salvador et al 2019), and Italian or Tibetan population (Rise et al 2008) whose main dietary oil is olive, sunflower, mustard, canola, and corn oil.…”
Section: Maternal and Cord Blood' Sfa Profilesupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, palmitic acid (C16:0) concentration was the highest among other SFAs in maternal and cord blood (Table 2). These findings are in line with previous studies which stated that palmitic acid is the principal constituent of fatty acids found in human tissues, such as in serum (Liu et al 2017;Yammine et al 2018), red blood cell (Aktas et al 2016), adipose tissue (Shramko et al 2020) and other human tissues in general (Ruiz-Nunez et al 2016). This pattern remains consistent when compared to Spanish vegetarian population (Salvador et al 2019), and Italian or Tibetan population (Rise et al 2008) whose main dietary oil is olive, sunflower, mustard, canola, and corn oil.…”
Section: Maternal and Cord Blood' Sfa Profilesupporting
confidence: 93%
“…Lauric acid (C12:0), one of the long-chain SFA, is less prone to β-oxidation than the shorter chain SFAs. It also can increase all cholesterol fractions, including triglyceride (Shramko et al 2020). It may explain the positive association of lauric acid level with infant adiposity indicators.…”
Section: Association Between Maternal and Cord Blood Sfa And Infant Adipositymentioning
confidence: 96%
“…Furthermore, although linoleate can be metabolized into arachidonic acid (AA), a PUFA precursor of eicosanoids which are a class of lipids including some with proinflammatory or prothrombotic-vasoconstrictor action, our previous analysis also showed the decrease of prostaglandin E2 [ 12 ], again leading to consider the treatment as anti-inflammatory. The reduction of hydroxylated species is relevant since the increased levels of these compounds are associated with pro-inflammatory cytokines production, vascular inflammation, and the development of cardiovascular diseases [ 53 ]. All together, these results demonstrate at the molecular level that LUT7-G shows anti-inflammatory properties with the regulation of metabolites important in endothelial and circulatory homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Among saturated fatty acids, palmitic acid content (C 16:0) was the highest in both meat and insects. It is included in the group of acids which are believed to have a negative effect on human body, especially by stimulating blood cholesterol-its LDL fraction in particular [63,64]. Among monounsaturated and polyunsaturated acids, the largest amount, in both meat and insects, was found in oleic (C 18:1) and linoleic acid (18:2 n-6).…”
Section: Discussionmentioning
confidence: 99%